Immune mechanism of n-butanol extract of Clerodendrum bungei against loach infected with Aeromonas hydrophila - Ya-Jie Li; Xin-Ya Dong; Hong-Hui Li; Hong-Hui Li; Jin-Guo Luo; Xing-Yu Chen; Xu-Dong Zhou (Frontiers in Immunology)
IntroductionTraditional Chinese medicines (TCMs) have a wide variety of chemical components and biological activities, which are applied in multiple fields such as medicine, agriculture and food. Clerodendrum bungei (C. bungei), known as “ChouMuDan” in Chinese, is a traditional herb belonged to the shrub of the genus Clerodendrum and used to treat various diseases. Previous studies indicated C. bungei had certain activity in antimicrobial aspects, therefore, the present study focus on exploring its antibacterial effect on loaches infected with A. hydrophila and the mechanism.MethodsThis study first prepared the n-butanol extract of C. bungei, using relux extraction and liquid-liquid organic partition method. Then, the loach was randomly divided into two groups. After the experiment, the livers of loaches from two different groups were dissected for microRNA sequencing. The samples were sequenced in Hiseq Single-End mode to obtain the original data. The Unique Reads were aligned with the non-coding RNA sequences in the Rfam 13 database using Blast to screen out the non-coding RNAs and identify their types and numbers for further analysis of their functions and regulatory mechanisms. The Reads Count value of miRNA was calculated, and the expression data of the conserved miRNA in each sample were sorted out. Finally, seven differentially expressed miRNA that regulate immunity, were selected to verify the credibility of miRNA expression identified by sequencing.ResultsTwo miRNA libraries of mCK1 and mC4 were constructed, using the Hiseq Single-End mode, to study the effect of n-butanol extract of Clerodendrum bungei Steud. (BECB) on loach infected with A. hydrophila. Differentially expressed miRNAs were identified, among which 9 were up-regulated and 17 were down-regulated. The cluster analysis of differentially expressed miRNAs showed that the expression pattern of miRNAs changed significantly after BECB treatment. KEGG enrichment analysis was carried out on target genes, and the top 30 most significantly enriched pathways were selected by p-value. The result suggested the immune-related pathways mTOR signaling pathway and RIG-I-like receptor signaling pathway may critical for resistance to A. hydrophila infection in loach after BECB treatment, together with RT-qPCR results.DiscussionIn this study, pathways related to carbohydrate and lipid metabolism were enriched after infection with A. hydrophila for 24 h, which may be because the proliferation and differentiation of immune cells require a large number of nutrients to provide energy. This indicates that pathogens did not appear in the loach until exposure to A. hydrophila for 24 h. After infection, both autophagy and mTOR signaling pathway are activated to promote the proliferation and differentiation of immune cells, induce the production of type I IFN and inflammatory factors, and then trigger innate and specific immunity. These findings could provide a basis for the research and development of antibacterial agents based on C. bungei and the application of biopesticides in aquaculture, especially in loach farming.